1999
DOI: 10.1002/(sici)1521-4141(199903)29:03<745::aid-immu745>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-resistant T cells have a deficiency in NF-κB-mediated induction of Fas ligand transcription

Abstract: Apoptosis induced through the TCR in CD4+ T cells is mostly mediated by the inducible expression of Fas ligand (FasL) as a primary event leading to the commitment to death. To gain a better understanding of the transcriptional events that regulate this expression, we took advantage of our previously described mutant Jurkat cells. These cells are deficient in FasL expression and apoptosis induced upon TCR triggering, although their cytokine (IL-2 and IFN-gamma) production is normal. Here we show that both a Fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
3
17
1
Order By: Relevance
“…AICD is a process in which IL-2 primes activated T cells for apoptosis (60) mediated by the interaction of Fas with FasL (61,62). Of relevance to our studies, the activation of NF-B is involved in the expression of Fas, FasL, and IL-2, and several studies have shown that blockade of NF-B antagonizes AICD (55,56,(63)(64)(65)(66). It is not clear why there is only an increase in the number of apoptotic cells and loss of lymphocytes in chronically infected mice, but long-term activated T cells are more sensitive to Fas-induced apoptosis than resting or short-term activated T cells (67,68).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…AICD is a process in which IL-2 primes activated T cells for apoptosis (60) mediated by the interaction of Fas with FasL (61,62). Of relevance to our studies, the activation of NF-B is involved in the expression of Fas, FasL, and IL-2, and several studies have shown that blockade of NF-B antagonizes AICD (55,56,(63)(64)(65)(66). It is not clear why there is only an increase in the number of apoptotic cells and loss of lymphocytes in chronically infected mice, but long-term activated T cells are more sensitive to Fas-induced apoptosis than resting or short-term activated T cells (67,68).…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have identified a clear role for NF-B proteins in the regulation of anti-apoptotic genes, such as TNFRassociated factor, cellular inhibitor of apoptosis, and IEX-1L (49 -53) although, recent studies indicate that NF-B can also have a pro-apoptotic role (54). Perhaps the most direct explanation for the increased apoptosis observed in the infected NF-B 2 Ϫ/Ϫ mice is that NF-B 2 Ϫ/Ϫ lymphocytes may have reduced expression of antiapoptotic factors and/or increased levels of proapoptotic proteins such as Fas, rendering these cells more susceptible to apoptosis (55)(56)(57)(58). However, to the best of our knowledge, NF-B 2 has not been associated with the regulation of apoptosis (20,21), and further studies will be required to determine whether NF-B 2 can regulate downstream targets that protect against apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DNA-damaging agents also induce expression of Fas ligand via activation of NF-kB in T lymphocytes (Kasibhatla et al, 1998). Interestingly, some apoptosis-resistant T cells have a de®ciency in NF-kB-mediated induction of FasL transcription (Teixeiro et al, 1999).…”
Section: Nf-kb As An Inducer Of Cell Deathmentioning
confidence: 99%
“…147 There is evidence that NF-B has a role in the induction of activation-induced apoptosis of T lymphocytes, however, this is not a direct role and appears to be due to the up-regulation of the FAS ligand on these cells. [148][149][150][151] Blocking NF-B translocation to the nucleus in CD34 + bone marrow cells prevents bone marrow cell colony formation and leads to the induction of apoptosis of these cells. 152 The cytoprotectant amifostine was reported to inhibit apoptosis in murine myeloid progenitor cells and human cord blood CD34 + cells.…”
Section: Nf-bmentioning
confidence: 99%